2013
DOI: 10.1103/physrevlett.110.237002
|View full text |Cite
|
Sign up to set email alerts
|

EuFe2(As1xPx)2: Reentrant Spin Glass and Superconductivity

Abstract: By systematic investigations of the magnetic, transport, and thermodynamic properties of single crystals of EuFe(2)(As(1-x)P(x))(2) (0≤x≤1), we explore the complex interplay of superconductivity and Eu(2+) magnetism. Below 30 K, two magnetic transitions are observed for all P substituted crystals, suggesting a revision of the phase diagram. In addition to the canted A-type antiferromagnetic order of Eu(2+) at ∼20  K, a spin glass transition is discovered at lower temperatures. Most remarkably, the reentrant sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 34 publications
9
80
0
Order By: Relevance
“…1 are consistent with previous results [11,15]. From the susceptibility we infer Eu 2+ spin ordering temperatures T N = 19 K and T C = 17.6 K in EuFe 2 As 2 (Eu-122) and EuFe 2 (As 0.81 P 0.19 ) 2 (EuP-122), respectively.…”
Section: A Samplessupporting
confidence: 79%
See 1 more Smart Citation
“…1 are consistent with previous results [11,15]. From the susceptibility we infer Eu 2+ spin ordering temperatures T N = 19 K and T C = 17.6 K in EuFe 2 As 2 (Eu-122) and EuFe 2 (As 0.81 P 0.19 ) 2 (EuP-122), respectively.…”
Section: A Samplessupporting
confidence: 79%
“…While no coherent picture of Eu 2+ spin ordering upon P or Co doping exists [4,[10][11][12], a pure FM ordering [12] coexisting with superconductivity was reported by Nandi et al [12] in EuFe 2 (As 0.85 P 0.15 ) 2 . Our recent transient magneto-optical spectroscopy study [13] also points towards the simple FM Eu 2+ spin order in the superconducting EuFe 2 (As 1−x P x ) 2 with a slow energy transfer between the FeAs-plane quasiparticles and Eu 2+ spins indicating a weak magnetic-dipole dominated coupling between the SC and FM order parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that the Eu 2+ moments order antiferromagnetically before the superconducting dome and ferromagnetically after the superconductivity is suppressed [20]. However, the exact nature of the Eu 2+ magnetic order within the superconducting dome remained controversial [22]. Most surprising is the coexistence of ferromagnetism and superconductivity as recently proposed by many groups for the P-doped EuFe 2 As 2 samples [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 97%
“…In particular, Zapf et al [22,26] concluded based on macroscopic measurements that the Eu 2+ moments in EuFe 2 (As 1−x P x ) 2 order in a canted A-type antiferromagnetic structure with the spin component along the c direction being ferromagnetically aligned. Zapf et al [22] also discovered that the A-type antiferromagnetic order of the Eu 2+ moments below around 20 K undergoes a spin glass transition at lower temperatures where the in plane components of the magnetic moments are responsible for the glassy freezing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation